Pengaruh Motivasi Ekstrinsik, Disiplin Kerja, dan Pengembangan Karir Terhadap Kinerja Karyawan PT. Raga Gunawan Mandiri - Rima Rima; Brahma Wahyu Kurniawan; Aprilia Dian Evasari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine the effect of extrinsic motivation, work discipline, and career development on the performance of employees of a limited liability company, Raga Gunawan Mandiri Kediri. This study uses a quantitative approach which the samples are taken from 31 permanent employees using a saturated sampling technique. The results of the data are obtained through interviews and questionnaires. Using analysis techniques such as validity test, reliability test, classical assumption test, multiple linear regression analysis, partial test (t), simultaneous test (f), and the coefficient of determination test, the results showed that extrinsic motivation, work discipline, and career development had a partial and simultaneous effect on the performance of employees at the limited liability company, Raga Gunawan Mandiri Kediri. The results of the coefficient of determination show that extrinsic motivation, work discipline, and career development affect the performance of 78.6% of employees at the limited liability company, Raga Gunawan Mandiri Kediri while the other 21.4% is influenced by variables other than the variables studied by researchers.